2013
DOI: 10.1517/14656566.2014.854771
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Janus kinases in rheumatoid arthritis: focus on tofacitinib

Abstract: Tofacitinib is a new class of DMARDs orally available with a new mechanism of action and with strong clinical efficacy similar to biologic DMARDs. Multiple cytokines and signaling pathways are partially inhibited at clinical doses that are in contrast to biological DMARDs. Further investigation is necessary to come to a conclusion on risk-benefit ratio and selection of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Despite that tofacitinib was initially described as a selective JAK3 inhibitor with 20-and 100-fold less potency in JAK2 and JAK1, respectively (Changelian et al, 2003), the compound was later on reported as a pan-JAK inhibitor less potent in TYK2 (Jiang et al, 2008;Meyer et al, 2010;Yamaoka and Tanaka, 2014) in line with our results. Data obtained internally for ruxolitinib showed that the compound is a pan-JAK inhibitor potent also in TYK2.…”
Section: Discussionsupporting
confidence: 86%
“…Despite that tofacitinib was initially described as a selective JAK3 inhibitor with 20-and 100-fold less potency in JAK2 and JAK1, respectively (Changelian et al, 2003), the compound was later on reported as a pan-JAK inhibitor less potent in TYK2 (Jiang et al, 2008;Meyer et al, 2010;Yamaoka and Tanaka, 2014) in line with our results. Data obtained internally for ruxolitinib showed that the compound is a pan-JAK inhibitor potent also in TYK2.…”
Section: Discussionsupporting
confidence: 86%
“…Tofacitinib was the first JAK3 inhibitor investigated in human trials and is approved by the US Food and Drug Administration for the treatment of rheumatoid arthritis, with the potential for expansion to other inflammatory and autoimmune diseases . Tofacitinib is also under clinical investigation for psoriasis, inflammatory bowel disease and prevention of transplant rejection .…”
Section: Tofacitinib As Treatment For Alopecia Universalismentioning
confidence: 99%
“…45 Moreover, expression of JAK3 is believed to be limited to T-, B-, NK and mast cells, 49,54,56,57 thus a JAK3 deficiency may cause immunodeficiency, although its specificity prevents pleiotropic defects. 58 Tofacitinib was the first JAK3 inhibitor investigated in human trials 58 and is approved by the US Food and Drug Administration for the treatment of rheumatoid arthritis, 59 with the potential for expansion to other inflammatory and autoimmune diseases. 60,61 Tofacitinib is also under clinical investigation for psoriasis, inflammatory bowel disease and prevention of transplant rejection.…”
Section: The Hair Follicle Is Immune-privileged Sitementioning
confidence: 99%
“…A number of TNF-α antagonists, such as infliximab, etanercept, adalimumab, golimumab and certolizumab pegol, have been developed and used in the treatment of RA 27 . The inhibitors of JAKs (e.g., tofacitinib and baricitinib) and spleen tyrosine kinase (SYK) (e.g., fostamatinib), have shown advantages in the interruption of kinase activities, thereby affecting intracellular signaling through kinase inhibition 54 . In this study, we identified a naturally sourced small molecule, NSM00191, that specifically disrupted the interaction between TRADD and TRAF2 (Figures 6 A, 6B and 6E), significantly reduced cell proliferation in vitro (Figure 6 D), and greatly improved inflammation status in RA mouse models (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%